Effectiveness of peripheral nerve blockage on the symptoms of both diseases in patients with fibromyalgia and chronic migraine coexistence - Evcili,Gokhan (2022)
SUMMARY OBJECTIVE: Peripheral nerve blockage treatments reduce central sensitization and are effective in patients with migraine. We wanted to evaluate the efficacy of peripheral nerve blockage in patients with fibromyalgia and migraine whose etiology may be responsible for central sensitization, and their associations are common. METHODS: The files of patients with chronic migraine who had peripheral nerve blockage treatment in our clinic and had fibromyalgia were scanned. The patients underwent bilateral great occipital nerve, lesser occipital nerve, and supraorbital nerve blockage at baseline and in the second week. The revised Fibromyalgia Impact Questionnaire, Migraine Disability Assessment Scale, Visual Analog Scale scores, the number of days in pain, and the number of analgesics taken in the last month were recorded. RESULTS: In the third month, Fibromyalgia Impact Questionnaire, Migraine Disability Assessment Scale, and Visual Analog Scale scores were significantly lower from baseline. While Fibromyalgia Impact Questionnaire scores in the third month were significantly lower than in the first month, no significant difference was observed between Visual Analog Scale scores. In the third month, the number of days in pain and the number of analgesics taken in the last month was significantly lower than the baseline but higher than the first month. CONCLUSION: Peripheral nerve blockage has been found to be an effective treatment for the symptoms of both diseases in patients with migraine and fibromyalgia coexistence.